A Novel Time Lag Method to Measure the Permeation of Vapor-Gas Mixtures - Chen, Jiahui; Loo, Leslie S.; Wang, Kean (Journal of Membrane and Separation Technology, 2012)
A novel time lag method was proposed to study the permeation of gas mixtures or vapor-gas mixtures. This technology, which is based on the difference in the boiling points of the components, can simultaneously measure the mass transport properties of each component. The permeation of a binary mixture of H2O(v)/CO2 was measured on a composite polymer membrane to demonstrate the feasibility of the technology. The method is low-cost and convenient for the future study of the permeation/separation of such gas mixtures as natural gas, flue gas, etc.